Respuestas

2014-01-04T14:36:16+01:00
 \frac{x(x-2a)}{\sqrt{bc} }  +  \frac{a-x}{\sqrt{c}}  - \frac{a-x}{\sqrt{b}}  = 1 - \frac{a^2}{\sqrt{bc}} \\
Multiplico \ por \ \sqrt{bc} \\
x(x-2a) +  \sqrt{b}(a-x) -  \sqrt{c}(a-x) =  \sqrt{bc} - a^2 \\ Despejo \ x \\
x^2 - 2ax + \sqrt{b}a - \sqrt{b}x - \sqrt{c}a + \sqrt{c}x = \sqrt{bc} - a^2 \\
Ordeno \ un \ poco \\
x^2 - x(2a + \sqrt{b} - \sqrt{c}) + a(\sqrt{b} - \sqrt{c}) + a^2 - \sqrt{bc}  = 0 \\
Ahora \ la \ cuadratica \\
x =  2a+\sqrt{b} -\sqrt{c} +- \sqrt{( 2a+\sqrt{b} -\sqrt{c})^2 - 4("c")
Comentario ha sido eliminado
Comentario ha sido eliminado
Comentario ha sido eliminado
see si no son dificiles son largos y fijate en no equivocarte en signos xd